Social cognition throughout the three phases of bipolar disorder: A state-of-the-art overview - Samame, Cecilia (2013)
Although it is now well documented that bipolar disorder (BD) often presents with cognitive deficits and suboptimal social adjustment, the social cognitive profile of the illness throughout its three phases remains unclear. An extensive search was conducted through the online databases EBSCO, PsychInfo, PubMed, ScienceDirect, and Wiley-Blackwell, covering the period between 1990 and 2012. Fifty-one studies comparing the social cognitive performance of bipolar patients with that of healthy controls were identified. Deficits in emotion recognition and theory of mind were found in manic, depressed, and euthymic bipolar subjects. Furthermore, altered face emotion recognition and brain-related abnormalities were noted both in euthymic patients and subjects at risk for BD. The influence of clinical and neurocognitive variables on the social cognitive performance of bipolar patients remains to be ascertained. Future directions for research are discussed.